KESENJANGAN TEKNOLOGI DAN EFISIENSI PRODUKSI KELAPA SAWIT RAKYAT DI SUMATERA - Varina, Firna; Tukidi, Tukidi (Agros Journal of Agriculture Science, 2024)
This study aims to compare technical efficiency (TE), technology gap ratio (TGR) and metafrontier technical efficiency (MTE) of oil palm smallholder oil palm in Sumatra according to their management patterns using data from the 2014 Estate Cultivation Household Survey by BPS-Statistics Indonesia. The result showed that the characteristics of oil palm smallholder production in Sumatra was on the Increasing Return to Scale. The average technical efficiency level of smallholders in Sumatra was 70% for the frontier, 69% for the metafrontier and a technology gap ratio of 99%.   The technical efficiency score for supported smallholders which was higher than the independent smallholders. There is still room to improve the management capabilities of independent smallholders by improving the education level of smallholders.